BULLYING FROM THE PERSPECTIVE OF HADITH IN THE SCHOOL ENVIRONMENT - Ria Zubaidah; Romlah Abubakar Askar; Abdul Ghofur (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Bullying is a deviant behavior that has serious impacts on the mental and social well-being of its victims, particularly within educational environments. From an Islamic perspective, acts of harming others—whether physically, verbally, or psychologically—are in direct contradiction to the values taught by the Prophet Muhammad (peace be upon him). This study aims to examine the perspective of hadith on bullying behavior and its relevance in shaping students’ character and social ethics. This research employs a library research method, with data obtained from primary hadith sources such as Sahih al-Bukhari, Sahih Muslim, and other supporting literature. The findings indicate that bullying is strongly prohibited in hadith, as it contradicts the principles of Islamic brotherhood (ukhuwah Islamiyah), the prohibition of harming others, and the obligation to uphold the dignity of fellow Muslims. The Prophet’s traditions guide Muslims to guard their speech and actions, avoid mockery, and build social relationships based on compassion and mutual respect. Therefore, the internalization of hadith values can serve as a fundamental basis for bullying prevention in educational settings.